+0  
 
0
303
2
avatar

Let f(x) = 2x + 7 and g(x) = 3x + c. Find c if \((f \circ g)(x) = (g \circ f)(x)\) for all x.

 Jul 19, 2017
 #1
avatar+27342 
+2

We have:

 

 2(3x+c) + 7 = 3(2x+7) + c

 

6x + 2c + 7 = 6 x + 21 + c

 

2c + 7 = 21 + c

 

c = 14

 

.

 Jul 19, 2017
 #2
avatar
0

Thank you!!

Guest Jul 19, 2017

10 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.